The role of thiol-disulfide and ischemia-modified albumin in the differential diagnosis of ovarian pathologies in children - Can Ihsan Oztorun; Gamze Gok; Ahmet Erturk; Sabri Demir; Dogus Guney; Alkim Oden Akman; Salim Neselioglu; Mujdem Nur Azili; Emrah Senel (Wolters Kluwer Medknow Publications, 2020)
Introduction: The aim of this study was to evaluate the association between ovarian pathologies and oxidative stress in children via the new method of thiol/disulfide homeostasis. Materials and Methods: The study was conducted in our clinic and included 24 cases of ovarian cysts (OCs) followed by us and 23 cases of operated OC or torsion and monitored by pediatric surgical intensive care unit. The control group consisted of 24 girls who admitted to the pediatric surgery outpatient clinic because of not-incarcerated inguinal hernia. Serum native thiol, total thiol, dynamic disulfide, albumin, and ischemia-modified albumin (IMA) levels of the patients and healthy volunteers were evaluated. Results: Native thiol (P = 0.41), total thiol (P = 0.57), dynamic disulfide (P = 0.98), albumin (P = 0.54), and IMA (P = 0.98) levels of the patients with OC were found similar with the ovarian torsion (OT) group. However, there were statistically significant differences in native thiol (P < 0.001), total thiol (P < 0.001), albumin (P < 0.001), and IMA (P < 0.001) levels of OT group compared to the controls, whereas dynamic disulfide levels (P = 0.63) were not statistically different from that of controls. Conclusions: In children, the evaluation thiol/disulfide homeostasis might be helpful in the diagnosis of ovarian pathology. Nonetheless, it could not be helpful in the differential diagnosis of OT, which requires emergency surgery from the other ovarian pathologies. Measuring of IMA levels as well as thiol/disulfide homeostasis could increase the specificity of the test. Further studies with larger samples are needed to clarify this issue.